THE EFFECT OF ISLAMIC BANKING FINANCING ON THE ENVIRONMENT QUALITY AT THE PROVINCES IN INDONESIA - Dewi Rahmawati Maulidiyah; Ilmiawan Auwalin (Jurnal Ekonomi Syariah Teori dan Terapan, 2021)
ABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh pembiayaan perbankan Syariah terhadap Indeks Kualitas Udara tingkat provinsi di Indonesia pada periode 2011-2018. Penelitian ini menggunakan pendekatan kuantitatif dengan teknik analisis regresi data panel. Data penelitian ini berjenis data sekunder yang bersumber dari KLHK, BPS, BPH Migas, OJK dan mencakup 33 provinsi di Indonesia. Hasil penelitian menunjukkan bahwa secara simultan pembiayaan perbankan syariah, kredit bank konvensional, konsumsi energi, PDRB Manufaktur, jumlah penduduk, luas kebakaran hutan dan lahan berpengaruh signifikan terhadap Indeks Kualitas Udara provinsi Indonesia tahun 2011-2018. Sedangkan secara parsial, pembiayaan perbankan Syariah memiliki hubungan negatif namun tidak signifikan terhadap Indeks Kualitas Udara dikarenakan market share masih kecil, pembiayaan yang dilakukan masih didominasi sektor konsumtif dan pengawasan OJK cenderung longgar sehingga pengawasan terhadap pembiayaan perbankan syariah baru sebatas tahap sebelum pembiayaan. Kredit bank konvensional dan konsumsi energi berpengaruh negatif signifikan terhadap Indeks Kualitas Udara serta luas kebakaran hutan dan lahan memiliki hubungan negatif namun tidak signifikan terhadap Indeks Kualitas Udara. Sedangkan jumlah penduduk berpengaruh positif signifikan terhadap Indeks Kualitas Udara serta PDRB Industri Manufaktur memiliki hubungan positif namun tidak signifkan terhadap Indeks Kualitas Udara.Kata Kunci: Pembiayaan Perbankan Syariah, Lingkungan Hidup, Indeks Kualitas Udara. ABSTRACTThis study aims to determine the effect of Islamic banking financing on Air Quality Index at the provincial level in Indonesia in 2011-2018 period. This study uses quantitative approach with panel data regression analysis techniques. This research data is secondary data, sourced from KLHK, BPS, BPH and includes provincial level data, namely 33 provinces in Indonesia. The results showed that simultaneously Islamic banking financing, conventional bank credit, energy consumption, manufacturing GDP, population, forest and land fires had significant effect on the Indonesian provincial Air Quality Index in 2011-2018. Meanwhile, partially, Islamic banking financing has a negative but insignificant relationship to the Air Quality Index because the market share is still small, the financing carried out is still dominated by the consumptive sector and OJK supervision tends to be loose so that supervision of Islamic banking financing is only limited to the stage before financing. Conventional bank credit and energy consumption have significant negative effect on the Air Quality Index and the area of forest and land fires has a negative but insignificant relationship to the Air Quality Index. Meanwhile, the population has a significant positive effect on the Air Quality Index and GDRP of the processing Industry has a positive but insignificant relationship to the Air Quality Index.Keywords: Islamic Banking Financing, Environment, Air Quality Index.DAFTAR PUSTAKAAbdouli, M., Kamoun, O., & Hamdi, B. (2018). The impact of economic growth, population density, and FDI inflows on CO 2 emissions in BRICTS countries: Does the Kuznets curve exist? Empirical Economics, 54(4), 1717–1742.Chen, B., Lu, S., Li, S., & Wang, B. (2015). Impact of fine particulate fluctuation  and other variables on Beijing’s air quality index. Environmental Science and Pollution Research, 22(7), 5139–5151. https://doi.org/10.1007/s11356-014-4024-zChen, D., & Chen, S. (2017). Particulate air pollution and real estate valuation : Evidence from 286 Chinese prefecture-level cities over 2004 – 2013. Energy Policy, 109(June), 884–897. https://doi.org/10.1016/j.enpol.2017.05.044Fan, J., & Zhou, L. (2019). Impact of urbanization and real estate investment on carbon emissions: Evidence from China’ s provincial regions. Journal of Cleaner Production, 209, 309–323. https://doi.org/10.1016/j.jclepro.2018.10.201Gujarati, D. N. (2004). Basic econometrics. 4th Edition, McGraw-Hill Companies.Hackett, C., & Lipka, M. (2018). The world’s fastest-growing major religious group. Scripta Instituti Donneriani Aboensis, 28, 11–14.Hanif, I., & Gago-de-santos, P. (2017). The importance of population control and macroeconomic stability to reducing environmental degradation: An empirical test of the environmental Kuznets curve for developing countries. Environmental Development, 23(December 2016), 1–9.  https://doi.org/10.1016/j.envdev.2016.12.003Iskandar, A., Possumah, B. T., & Aqbar, K. (2020). Islamic financial development, economic growth and CO2 emission in indonesia. Journal of Islamic Monetary Economics and Finance, 6(2). https://doi.org/10.21098/jimf.v6i2.1159Kementerian Agama Republik Indonesia. (2017). Al-Qur’an dan terjemahannya. Jakarta: Kemenag RI.Nasution, R. (2018). Synergy and optimization of sharia banking green banking in realizing suistainable finance. Jurnal Ilmu Ekonomi Dan Studi Pembangunan, 18(1), 33–52Nwani, C., & Omoke, P. C. (2020). Does bank credit to the private sector promote low-carbon development in Brazil ? An extended STIRPAT analysis using   dynamic ARDL simulations. Environmental Science and Pollution Research, 31408–31426. https://doi.org/https://doi.org/10.1007/s11356-020-09415-7